Esophageal Sensorimotor Function and Psychological Factors Each Contribute to Symptom Severity in Globus Patients. (October 2016) - Rommel, Nathalie; Van Oudenhove, Lukas; Arts, Joris; Caenepeel, Philip; Tack, Jan; Pauwels, Ans
Abstract : OBJECTIVES: Altered upper esophageal sphincter (UES) and esophageal body (EB) sensorimotor function and psychosocial factors may both be involved in symptom generation in globus, but their common impact is not yet assessed. The aim of the study is (1) to compare UES and EB sensitivity and compliance of globus patients with healthy controls (HC); (2) to study the association of globus symptom severity (GSS) with UES and EB sensitivity and compliance, UES motor function and psychosocial factors. METHODS: In 58 globus patients, GSS, somatization, and anxiety disorders were determined using validated questionnaires. In 26 HC and 42/58 patients, UES and EB sensitivity and compliance were assessed twice using barostat measurements. UES function of 27 globus patients was evaluated using high‐resolution manometry. Bivariate correlations and a general linear model tested the association of these factors with GSS. RESULTS: UES and EB compliance did not differ between globus patients and HC. Upon repeated distension, UES habituation was seen in both groups, whereas EB sensitization (23.3±1.3 vs. 19.5±1.5 mm Hg, P <0.0001) only occurred in globus patients, ( P =0.038). UES compliance ( ρ =0.37, P =0.04), change in EB compliance upon repeated distension ( ρ =0.45, P =0.007), somatization ( ρ =0.43, P =0.003), panic disorder ( t =3.04, P =0.004), and post‐traumatic stress severity ( ρ =0.40, P =0.005) were associated with GSS. UES compliance and somatization were independently associated with GSS. A trend ( P =0.061) was found for the association of GSS with change in EB compliance. CONCLUSIONS: UES compliance, change in EB compliance, and somatization explain 40% of the variance in GSS. This indicates that globus is a complex disorder of the brain‐gut axis rather than a "psychosomatic" disorder or a peripheral esophageal disorder.